Investigating the nonlinear effect of ego depletion on safety compliance: The moderating role of rumination. (December 2018) - Chen, Ming; Chen, Long; Yan, Xiao-Ming; Yu, Zhuo; Fang, Ying-Ying; Yu, Yan-Qiu
Abstract: Introduction: A general view in previous research is that employees are reluctant to follow safe work procedures when confronting the shortage of self-control resources. However, this argument is constrained by the restricted view of ego depletion. To fill this gap, this study constructs the nonlinear relationship between ego depletion and safety compliance drawing from the perspective of dual-process theory. Method: Regression analysis and hierarchical linear model are used to test our hypothesis. Results: By investigating 241 medical staffs, we find that the relationship between ego depletion and safety compliance is U-shaped. This U-shaped relationship is replicated through 221 daily data for 50 medical staffs. In addition, the U-shaped relationship between ego depletion and safety compliance can be enhanced by rumination. Discussions: Findings of our study contribute to providing a nuanced explanation about the effect of ego depletion on safety compliance. Also, this study has important implications for High Reliability Organizations to motivate depleted employees to engage in safety compliance behaviors. Highlights: This study explains a U-shaped relationship between ego depletion and safety compliance. Rumination can strengthen such U-shaped relationship. Findings of this study demonstrate the value of ego depletion and rumination.